PERAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK TERHADAP TINDAK KEKERASAN ANAK DI KOTA MAKASSAR (PERDA NOMOR 5 TAHUN 2018 TENTANG PERLINDUNGAN ANAK) - Sumiati; Imam Suyitno; Bakhtiar (CV. Kalimasada Group, 2023)
This study aims to obtain an overview of: (i) the factors that influence the occurrence of acts of violence against children in Makassar City, (ii) the efforts made by the Women's Empowerment and Child Protection Service (DP3A) in protecting children who experience acts of violence, and ( iii) DP3A achievements in implementing Makassar City Regional Regulation Number 5 of 2018 concerning Child Protection. The research approach used is a qualitative approach, type of descriptive research, carried out by examining data based on facts aiming to explore data and information sourced from the DP3A Office and related agencies in order to obtain accurate and valid data. The results of the study show that: (i) The factors that influence the occurrence of acts of violence against children in Makassar City are family, economic, peer environment, and social media; (ii) the efforts taken by the DP3A are establishing residents' shelters, collaborating with various institutions/agencies, creating programs for the protection and prevention of violence against children, and maximizing the socialization of Regional Regulation Number 5 of 2018; and (iii) the achievements of the Makassar City DP3A in implementing Regional Regulation Number 05 of 2018 concerning Child Protection are the achievement of the strategic targets of fulfilling children's rights, the fulfillment of the realization of targets for achieving program performance and activities in 2021, and the reduction in cases of violence against children since the issuance of the Makassar City Regional Regulation Number 05 of 2018 concerning Child Protection.